2018
DOI: 10.2147/bctt.s166135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SnapChat mobile social networking application for breast cancer awareness among Saudi students in the Dammam Region of the Kingdom of Saudi Arabia

Abstract: PurposeThe main aim of this study was to investigate the feasibility and the effectiveness of the SnapChat social networking mobile application in increasing the awareness of breast cancer among the Saudi female students in the Dammam region of Saudi Arabia.Patients and methodsAn intervention study was carried out with 200 participants divided among 2 groups: a control group and an intervention group. The control group did not receive any awareness materials, and the intervention group received awareness about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…SnapChat , a social networking mobile app used to deliver educational material on breast cancer through videos, texts, and pictures, increased breast cancer awareness among female students in the Dammam region of Saudi Arabia [23]. Eden et al [24] studied decisional conflict and self-efficacy in 75 women before and after the use of a mammography screening decision aid in the form of an mHealth app and showed that the use of the mHealth app decreased the decisional conflict and increased the decisional self-efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…SnapChat , a social networking mobile app used to deliver educational material on breast cancer through videos, texts, and pictures, increased breast cancer awareness among female students in the Dammam region of Saudi Arabia [23]. Eden et al [24] studied decisional conflict and self-efficacy in 75 women before and after the use of a mammography screening decision aid in the form of an mHealth app and showed that the use of the mHealth app decreased the decisional conflict and increased the decisional self-efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…We identified three common themes for the use of mobile health apps in primary breast cancer prevention: knowledge and adherence to screening guidelines, the targeting of high-risk populations, and the incorporation of theoretical frameworks. Primary prevention studies focused on apps that increased breast cancer prevention knowledge and adherence to breast cancer guidelines and surveillance (77, 79, 80, 8385). Six of the 9 studies used existing guidelines to inform their apps (77, 80, 81, 83, 85).…”
Section: Resultsmentioning
confidence: 99%
“…Primary prevention studies focused on apps that increased breast cancer prevention knowledge and adherence to breast cancer guidelines and surveillance (77, 79, 80, 8385). Six of the 9 studies used existing guidelines to inform their apps (77, 80, 81, 83, 85). For example, in designing an app to help women reduce their risk of breast cancer through healthy behaviors, Coughlin et al (81) included evidence-based information provided by the National Cancer Institute, the Centers for Disease Control and Prevention, and the American Cancer Society.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in [10], the study was about examining how Saudi youth engagements with online social networks are formed and constrained within the cultural and religious aspects of this region. Meanwhile, others were assessing the effectiveness of Snapchat in raising the awareness of breast cancer among Saudi female students in the Dammam region [11].…”
Section: Introductionmentioning
confidence: 99%